Three CoA Transferases Involved in the Production of Short Chain Fatty Acids in Porphyromonas gingivalis - Sato, Mitsunari; Yoshida, Yasuo; Nagano, Keiji; Hasegawa, Yoshiaki; Takebe, Jun; Yoshimura, Fuminobu (Frontiers in Microbiology, 2016)
Butyryl-CoA:acetate CoA transferase, which produces butyrate and acetyl-CoA from butyryl-CoA and acetate, is responsible for the final step of butyrate production in bacteria. This study demonstrates that in the periodontopathogenic bacterium Porphyromonas gingivalis this reaction is not catalyzed by PGN_1171, previously annotated as butyryl-CoA:acetate CoA transferase, but by three distinct CoA transferases, PGN_0725, PGN_1341, and PGN_1888. Gas chromatography/mass spectrometry (GC-MS) and spectrophotometric analyses were performed using crude enzyme extracts from deletion mutant strains and purified recombinant proteins. The experiments revealed that, in the presence of acetate, PGN_0725 preferentially utilized butyryl-CoA rather than propionyl-CoA. By contrast, this preference was reversed in PGN_1888. The only butyryl-CoA:acetate CoA transferase activity was observed in PGN_1341. Double reciprocal plots revealed that all the reactions catalyzed by these enzymes follow a ternary-complex mechanism, in contrast to previously characterized CoA transferases. GC-MS analysis to determine the concentrations of short chain fatty acids (SCFAs) in culture supernatants of P. gingivalis wild-type and mutant strains revealed that PGN_0725 and PGN_1888 play a major role in the production of butyrate and propionate, respectively. Interestingly, a triple deletion mutant lacking PGN_0725, PGN_1341, and PGN_1888 produced low levels of SCFAs, suggesting that the microorganism contains CoA transferase(s) in addition to these three enzymes. Growth rates of the mutant strains were mostly slower than that of the wild type, indicating that many carbon compounds produced in the SCFA synthesis appear be important for the biological activity of this microorganism.